رقابة قضاء المظالم على أعمال الإدارة في المملكة العربية السعودية وتمييزها عن رقابة قضاء المظالم في النظام الإسلامي Grievances of Judiciary Supervision of Administrative Works in Saudi Arabia and Differentiating them from the Grievances of Judiciary - آل يحيى سلطان بن حسن; إبراهيم بدر الدين; ليبا محمد (Journal of Islam in Asia (E-ISSN 2289-8077), 2016)
الملخّص يذهب فقهاء القانون الإداري إلى اعتبار الرقابة القضائية على أعمال الإدارة وتصرفاتها أهم وسيلة للمحافظة على مبدأ المشروعية، وهو المبدأ الذي يضمن للأفراد حقوقهم وللإدارة استقرارها. وفي هذا السياق؛ تأتي هذه الدراسة لتسليط الضوء على القواعد العامة التي يمارس من خلالها ديوان المظالم في المملكة العربية السعودية رقابته على نشاط الإدارة المتمثل في تنفيذ الأنظمة واللوائح وتشغيل المرافق العامة. وسيتم ذلك من خلال استعراض اختصاصات المحاكم الإدارية التابعة لديوان المظالم بفئاتها الثلاث: المحكمة الإدارية العليا، ومحاكم الاستئناف الإدارية، والمحاكم الإدارية (محاكم الدرجة الأولى)، ثم يلي ذلك بحث حدود النطاق الولائي لرقابة القضاء الإداري السعودي على النشاط الإداري، وسيكون السير في هذا المضمار من خلال محاولة شرح النصوص وتفسير الغامض منها، والإفادة من الأحكام القضائية كحالات عملية، لتنتهي الدراسة بعد ذلك باستعراض الحالات المهمة في تمييز قضاء المظالم في النظام الإسلامي عن قضاء المظالم في النظام السعودي. الكلمات المفتاحيّة: ديوان المظالم، القضاء الإداري، الرقابة القضائية، جهة الإدارية. Abstract Jurists of administrative law consider judicial supervision of administrative works and their actions one of the means of preserving the principle of legitimacy, which ensures the rights of individuals as well as the organization’s stability. This study attempts to shed light on the applied general principles through which the Bureau of Grievances in the Kingdom of Saudi Arabia exercises its supervision of management activities reflected by the implementation of the systems and rules and operating public facilities. This paper accomplishes through a demonstration of the tasks of administrative courts that work under the Bureau of Grievances in its three sections: the Supreme Administrative Court, Administrative Courts of Appeal, and Administrative Courts (courts of first instance), followed by a discussion on the scope of the Supervision of the Saudi administrative judiciary and administrative activities, illustrating cases for differentiating grievances of judiciary in Islamic system from grievances of judiciary in the Saudi system. Keywords: Bureau of Grievances, Administrative Judiciary, Judicial Supervision, Administrative Authority.